지질혈증 검체의 헤모글로빈 농도 측정에서 생리식염수 치환 검사법을 대체할 세포 헤모글로빈 농도 사용의 임상적 유용성 - 박수응; 김혜진; 이진경; 홍영준; 오애진; Soo Eung Park; Heyjin Kim; Jin Kyung Lee; Young Jun Hong; Ae-Chin Oh (Laboratory Medicine Online, 14(1), 2024)
Hemoglobin transports oxygen and carbon dioxide and is often measured via turbidimetry. However, lipemia interferes with turbidimetry results; therefore, the saline replacement method is required to overcome this interference. The ADVIA® 2120i hematology system (Siemens Healthineers, Germany) measures cellular hemoglobin using the mean cellular hemoglobin concentration, measured via flow cytometry. Lipemia does not interfere with flow cytometry results. De-identified lipemic samples assessed with ADVIA® 2120i from March 2018 to March 2023 were analyzed for hemoglobin and cellular hemoglobin levels in comparison with age-matched controls. Similarly, patient sex and age were compared. First, analysis of variance and a post-hoc analysis were performed to compare mean hemoglobin, cellular hemoglobin, and saline-replacement hemoglobin levels in lipemic samples. Subsequently, receiver operating characteristic curve analysis was performed to elucidate the specific cutoff hemoglobin minus cellular hemoglobin level in lipemic and control samples. Complete blood count was performed for 667,532 samples, 394 (0.06%) of which were lipemic. In lipemic samples, the mean hemoglobin and cellular hemoglobin levels differed significantly (P<0.001). However, the mean cellular and saline-replacement hemoglobin levels did not differ significantly (P=0.990). A cutoff hemoglobin minus cellular hemoglobin level of 0.35 g/dL had a sensitivity of 90.9% and specificity of 97.5%. The results suggest that when ADVIA® 2120i-measured hemoglobin minus cellular hemoglobin level is ≥0.35 g/dL in lipemic samples, cellular hemoglobin levels can be used in the final report of hemoglobin level without performing saline replacement method. 혈색소(hemoglobin, Hb)란 적혈구에 존재하며 혈액 속에서 산소를 운반하는 주된 매개체인 붉은색 단백질을 지칭한다. Hb는 일반적으로 지질혈증 검체에 의해 검사결과에 영향을 받을 수 있는 흡광도법을 사용하여 측정되며, 이러한 영향을 극복하기 위하여 수기로 시행하여야 하는 생리식염수 치환 검사법이 필요하였다. 한편, ADVIA® 2120i (Siemens Healthineers, Germany) 자동혈구분석기에서는 세포 Hb라고 지칭되는 특징적인 검사결과를 제공하고 있다. 이 검사결과는 세포혈색소농도평균이라고 지칭되는 고유한 수치를 측정하여 산출되는 값이며, 유세포분석법으로 측정하므로 지질혈증 검체로 인한 결과의 영향을 받지 않는다. 2018년 3월부터 2023년 3월까지 단일 기관에서 ADVIA® 2120i 자동혈구분석기를 사용하여 검사한 지질혈증군과 이와 성별, 연령을 일치시킨 대조군이 본 연구에 사용되었다. 본 연구팀은 우선 지질혈증군에서 Hb, 세포 Hb 및 생리식염수 치환 후 Hb 간의 평균에 유의한 차이가 있는지 확인하였다. 이후, ROC 곡선을 이용하여 Hb 농도에서 세포 Hb 농도의 차를 이용한 컷오프 검정을 시행하였다. 해당 기간 동안 검사된 667,532예의 검사결과 중 394예(0.06%)가 지질혈증 검체로 판정되었다. 지질혈증군에서 시행한 ANOVA에서 Hb 농도와 세포 Hb 농도 간의 평균과 Hb 농도와 생리식염수 치환 후 Hb 농도 간의 평균은 유의한 차이(P<0.001)를 보였으며, 세포 Hb 농도와 생리식염수 치환 후 Hb 농도 간의 평균은 유의한 차이를 보이지 않았다(P=0.990). ROC 곡선을 이용한 컷오프 검정에서 Hb 농도에서 세포 Hb 농도의 차가 0.35 g/dL인 경우가 가장 이상적인 컷오프로 선정되었으며 이때의 민감도는 90.9%, 특이도는 97.5%를 나타내었다. 본 연구에서 도출된 결과를 토대로, 본 연구팀은 자동혈구분석기에서 Hb 농도에서 세포 Hb 농도를 뺀 값의 차가 0.35 g/dL 이상인 검체에서는 생리식염수 치환 없이 세포 Hb 농도를 Hb 농도로 보고할 것을 제안하는 바이다.